2002
DOI: 10.1007/s00266-002-1359-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Vitamin Pool (Vitamins A, E, and C) on the Tissue Necrosis Process: Experimental Study on Rats

Abstract: During surgical procedures on the epidermis, either aesthetic or reconstructive, the medical literature shows that certain technical standards and skin flap proportions should be followed, unless the risk of necrosis increases, in different degrees, directly related to the trauma. This study evaluates the evolution of skin flaps on the dorsum of rats treated with a vitamin pool (VP) (vitamins A, E, and C). Twenty-six rats, divided into two groups, were used: (A) the treated group (13 specimens), in which we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…In addition, vitamin C aids in improving immune function particularly during infection 24, 180. The use of vitamins E and C acid has been reported to help accelerate wound healing 181. Vitamin E is also capable of preserving important morphological and functional features of biological membranes159 though its use in topical applications has however, been discouraged due to the problem of contact dermatitis 182.…”
Section: Medicated Dressings For Drug Deliverymentioning
confidence: 99%
“…In addition, vitamin C aids in improving immune function particularly during infection 24, 180. The use of vitamins E and C acid has been reported to help accelerate wound healing 181. Vitamin E is also capable of preserving important morphological and functional features of biological membranes159 though its use in topical applications has however, been discouraged due to the problem of contact dermatitis 182.…”
Section: Medicated Dressings For Drug Deliverymentioning
confidence: 99%
“…In the etiology of the I/R injury, a vascular thrombosis secondary to an imperfect technique, former disease in recipient or donor vessel (atherosclerosis), poor selection of recipient vessel (within the zone of injury and prone to spasm), arterial hypotension or a hypercoagulable state are contributory processes. Whatever the etiology, there have been two approaches to try to rescue the free flap: (a) early detection and rectification of the problem; (b) improvement of flap tolerance to I/R injury [1] by exogenous application of superoxide dismutase (SOD), allopurinol [7], catalase (CAT) [8], vitamin C [9], vitamin E, vitamin A [10], dexamethasone [11], heparin [12], deferroxamine [13], sulfatide [14], aprotinin [15], monoclonal antibodies [16], fucoidin [17], and melatonin [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on antioxidants were found to improve healing ability. [1617] Success in the present study shows that a combination of antioxidants comprising Vitamin A, B, and C along with trace elements like zinc are capable in radicular tissue repair and regeneration.…”
Section: Discussionmentioning
confidence: 61%